Obesity and Low-Grade Inflammation Increase Plasma Follistatin-Like 3 in Humans. (3rd July 2014) - Brandt, Claus; Pedersen, Maria; Rinnov, Anders; Andreasen, Anne S.; Møller, Kirsten; Hojman, Pernille; Pedersen, Bente K.; Plomgaard, Peter
Abstract : Background . Rodent models suggest that follistatin-like 3 (fstl3) is associated with diabetes and obesity. In humans, plasma fstl3 is reduced with gestational diabetes. In vitro, TNF- α induces fstl3 secretion, which suggests a link to inflammation. Objective . To elucidate the association between plasma fstl3 and obesity, insulin resistance, and low-grade inflammation in humans. Study Design . Plasma fstl3 levels were determined in a cross-sectional study including three groups: patients with type 2 diabetes, impaired glucose tolerance, and healthy controls. In addition, lipopolysaccharide (LPS), TNF- α, or interleukin-6 (IL-6) as well as a hyperinsulinemic euglycemic clamp were used to examine if plasma fstl3 was acutely regulated in humans. Results . Plasma fstl3 was increased in obese subjects independent of glycemic state. Moreover, plasma fstl3 was positively correlated with fat mass, plasma leptin, fasting insulin, and HOMA B and negatively with HOMA S. Furthermore plasma fstl3 correlated positively with plasma TNF- α and IL-6 levels. Infusion of LPS and TNF- α, but not IL-6 and insulin, increased plasma fstl3 in humans. Conclusion . Plasma fstl3 is increased in obese subjects and associated with fat mass and low-grade inflammation. Furthermore, TNF- α increased plasma fstl3, suggesting that TNF- α is one of the inflammatory drivers of increased systemic levels of fstl3.